Odpowiedź :
sinα - cosα = 7/8
(sinα - cosα)² = (7/8)²
(sinα - cosα)² = 49/64
sin²α - 2 * sinα * cosα + cos²α = 49/64
(sin²α + cos²α) - 2 * sinα * cosα = 49/64
1 - 2 * sinα * cosα =49/64
2 * sinα * cosα = 15/64
sinα * cosα = 15/128
(sinα - cosα)² = (7/8)²
(sinα - cosα)² = 49/64
sin²α - 2 * sinα * cosα + cos²α = 49/64
(sin²α + cos²α) - 2 * sinα * cosα = 49/64
1 - 2 * sinα * cosα =49/64
2 * sinα * cosα = 15/64
sinα * cosα = 15/128
sina - cosa = 7/8
( sina - cosa ² = ( 7/8 )²
sin² a - 2*sina*cosa + cos ² a = 49/64
(sin²a+cos²a)-2*sina*cosa = 49/64
1-2*sina*cosa = 49/64
2*sina* = 15/64
sina*cosa = 15/128
( sina - cosa ² = ( 7/8 )²
sin² a - 2*sina*cosa + cos ² a = 49/64
(sin²a+cos²a)-2*sina*cosa = 49/64
1-2*sina*cosa = 49/64
2*sina* = 15/64
sina*cosa = 15/128